Mapping Barriers to the Implementation of Public Policy Oversight Functions by the DPRD in Dumai City - Hidayati, Hidayati; Nazir, Yendri; Adni, Dita Fisdian (Jurnal Pemerintahan dan Politik Lokal, 2024)
This study aims to identify the main obstacles faced by the Dumai City Regional People's Representative Council (DPRD) in its supervisory function over public policy-making at the regional level. The research method used was secondary data analysis and a survey of members of the Dumai City DPRD. The findings show that the DPRD faces several monitoring obstacles, including dependence on local government, an imbalance of political power, limited resources, limited access to information, and a need for more awareness and skills in carrying out supervision. These findings imply the need for strategic action to minimize dependence on local governments, strengthen legislative control, more adequate resource allocation, and increase information disclosure and training for DPRD members. By overcoming these obstacles, the Dumai City DPRD can carry out its oversight role more effectively and contribute to good governance at the regional level.